OC-099 The two-week clinic for bowel cancer isn't working; a re-audit of referrals twelve years on. (22nd June 2015) - Flashman, K; Ellis, B; O'Leary, D; Senapati, A; Thompson, MR
Abstract : Introduction: Considerable resources have been used to achieve DOH targets for Two-week Colorectal Clinics (TWC) but few studies have monitored the increase in referrals, the decrease in diagnostic yield (DY) of referral criteria and whether this costly strategy has improved outcomes. Method: A prospective study of the numbers referred to the TWC in Portsmouth for each of the referral criteria and the DY for bowel cancer in 2013/14 compared with 2000/1. 1 Results: The last 12 years has seen a 235% increase (695 1 to 1636 2 ) in referrals to the TWC, compared to a 130% increase (1815 1 to 2404 2 ) in routine clinics. 41% of all new patient referrals to surgical clinics are to the TWC, compared to 27% in 2000/1. An extra 194 clinics per year are required to see these patients. DY for cancer in the TWC has fallen from 9.4% (65/695) to 4.1% (20/487). The greatest fall was for patients referred with a change in bowel habit with rectal bleeding. Conclusion: A doubling in outpatient staff has been required to cope with the increase in referrals to the TWC. There has been a decrease in adherence to the TWC referral criteria, particularly change in bowel habit, resulting in a DY of 1.8% (3/170) for patients referred with C+B-. Unless this is improved there is little point in continuing with the TWC. Disclosure of interest: None Declared. References: Flashman K, O'Leary DP, Senapati A, Thompson MR. The Department of Health's 'two-week standard' for bowel cancer: is it working? Gut 2004;53(3):387–391 Estimate from numbers for 3 months